Cell Viability of Bifidobacterium Under Freeze Drying, Storage and Gastrointestinal Tract Simulation by Microencapsulation - Shamekhi, Seyedeh Fatemeh (2011)
Nowadays, it is well known that many infants in the world who are deprived of breast feeding and in the face of high incidence of multiple gut related diseases, need to be supplied with a formula capable of substituting breast milk’s synbiotic properties. The purpose of this research was to improve the viability of probiotic bacteria (Bifidobacterium lactis DSM 10140 and Bifidobacterium infantis DSM 20088) during freeze-drying process, storage period and infantile gastrointestinal tract (GIT) conditions by microencapsulation using prebiotics. Special emphasis was given to the use of pediatrics recommended prebiotics mixture including galactooligosaccharides (GOS) and fructooligosaccharides (FOS). Initially, probiotic microorganisms were encapsulated with a coat combination of prebiotics-calcium-alginate prior to freeze-drying, using emulsion technique. Glycerol was used as cryo-protectant to enhance the survival of beads over freeze-drying. Both encapsulated and free cells were then freeze dried in their optimized combinations of skim milk and prebiotics as freezing media. Statistical optimization techniques were used to produce a coating combination as well as drying medium for each strain with the highest survival during freeze-drying. The interactive effects of Na-alginate, prebiotics and glycerol as well as skim milk and prebiotics on the viability of encapsulated and free cells were determined respectively. The statistical optimizations were performed based on Response Surface Methodology (RSM). The inputs, percentage survival, were derived experimentally and tested by RSM. The optimum compositions for encapsulation of B. lactis and B. infantis derived via RSM analysis were: Na-alginate 2.1% and 2.9%, prebiotic 2.9% and 2.7% and glycerol 21.7% and 25.4%, respectively. Maximum survival of encapsulated B. lactis and B. infantis, predicted by models during freeze drying were 81.2% and 72.1%, whereas those of free cells (as control) were 62.1% and 47.6%, respectively. No significant (p > 0.05) difference between the predicted and experimental values verified the adequacy of all final reduced models fitted by RSM. The protective effects of encapsulation on survival rates of cells as compared to free cells were evaluated over a storage period. After 120 days of storage of encapsulated cells at 4°C, there was about 1 log10 cfu/ml improvement in the viability of both strains as compared to free cells. Also, two different simulated infantile GIT conditions including gastric conditions (pH 3.0 and 4.0, 90 min, 37ºC) and intestinal conditions (pH 7.5, 5h, 37ºC) in a sequential model were conducted for assessment of both free and encapsulated cells’ survival. The mortality rates of encapsulated B. lactis 10140 after sequential incubation in simulated GIT conditions, when it had passed the gastric juice at pH 3.0 and 4.0 were reduced by 1.28 and 0.5 log10 cfu/ml, as compared to those of free cells. For B. infantis 20099, these reduction rates were 2.14 and 1.47, respectively. From this study, it can be concluded that microencapsulation of B. lactis 10140 and B. infantis 20088 using prebiotics, was a successful effort to produce a stable synbiotic powdery nutraceutical.